Effect of using Tithonia diversifolia green manure and Trichoderma sp. secondary metabolites on the growth and yield of tomato plants (Solanum lycopersicum L.) on alluvial soil / Agus Suyanto, Setiawan and Ismail Astar - Suyanto, Agus; -, Setiawan; Astar, Ismail (Universiti Teknologi MARA, Sarawak, 2024)
The primary challenge in utilising alluvial land for tomato cultivation was the low soil fertility. Tithonia diversifolia can be used as an ameliorant to address this issue. Additionally, secondary metabolites from Trichoderma sp. can be employed to control plant diseases. This research aimed to assess the impact of using Tithonia diversifolia green manure and Trichoderma sp. secondary metabolites on the growth and yield of tomato plants in alluvial soil. The research was conducted in the experimental field of the Faculty of Agriculture, Science, and Technology, Panca Bhakti University Pontianak, from December 2023 to March 2024. A factorial completely randomised design (CRD) was implemented, involving two factors: the first factor was T. diversifolia green manure (p) with three treatment levels: p1 = 200 g per polybag, p2 = 250 g per polybag, p3 = 300 g per polybag. The second factor was Trichoderma sp. secondary metabolites (m) with three treatment levels: m1 = 100 mL per plant, m2 = 150 mL per plant, m3 = 200 mL per plant. Observations focused on plant growth and yield. Data were analysed using the F-test and Tukey test at the 5% significance level. The application of 300 g of Tithonia diversifolia green manure and 200 mL of Trichoderma sp. secondary metabolites can enhance the growth and yield of tomato plants optimally in alluvial soil, although no significant interaction was observed (p > 0.05). Further research is needed to identify other factors that influenced the interaction so that the use of Tithonia diversifolia green manure and Trichoderma sp. could be recommended to increase tomato productivity in alluvial soil.